Zoo Design for Learning and Promoting Awareness Toward the Livings - ศุกลรัตนเมธี, สินีนาถ (NAJUA: Architecture, Design and Built Environment, 2018)
Zoo Design for Learning and Promoting Awareness Toward the Livings Sineenart Sukolratanametee Department of Urban Design and Planning, Faculty of Architecture, Silpakorn University Zoo is a unique and valuable public place which serves four primary roles: recreation, education, research, and conservation. Although, the recreational role of a zoo seems to predominate the others, any enhancement of such role through creation of entertaining experience can turn a zoo from merely a place for animal exhibition to a place of learning. This article explores the evolution of zoological design from its early period where animals are displayed in cage barriers for entertaining purposes, to newer trends where animals and visitors are immersed into the same environment, designed to enrich visitor experience and animal welfare. These trends aim to educate public through exhibition design and to enhance their learning experience through stimulation of human cognitive process. Examples of newer design trends are; activity-based design where behavioral enrichment design is used to encourage animal activities resulting in more attractive display; affiliative design which aim to create human empathy with animals through enhancement of natural bonding between human and animals; and the newer idea attempting to have visitors and animals in the same habitat, thus experiencing the same things. The evolution explicitly delivers a message of a changing viewpoint toward human role in the environment from homocentricity to biocentricity. Therefore, zoo design can be used to enforce human learning process and also to promote public awareness on the ethics toward nature and wildlife. As such, zoo can become a place of learning that allows visitors to observe, interpret, evaluate, and learn from its content as well as its message conveying co-existence of the livings in the world.